An experimental study on the movement characteristics of a social group in unidirectional flow. (1st January 2023) - Hu, Yanghui; Ren, Xiangxia; Zhang, Jun; Song, Weiguo
Abstract : Investigating the pedestrian dynamics can help researchers and managers design pedestrian facilities more reasonably and develop crowd management plans scientifically. Researches show that most pedestrians in the crowd are a social group that has an impact on pedestrian movement characteristics in normal and emergency situations. In this study, a series of unidirectional-flow experiments are carried out to investigate the influence of a two-people social group with a strong relationship on pedestrian flow via changing corridor structures and components of the crowd. It is found that there are significant statistical differences between social groups and individuals at the micro-level, such as personal space. However, such differences are not reflected in the macro level, the presence of the social group has no significant impact on pedestrian dynamics, such as fundamental diagram and movement time. In addition, social groups adjust their relative positions and distance to alleviate the influence of high density.